(3GdCMcGe GdTQYjI GdUZQis - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO YHO GdMb GdCROi QVi Gddg Yfg GdMeO ddg QH GdYGdejf CeG HYO aEfi bO LeYJ ai gPG GdcJGH eJaQbG ef MOjK QShd Gddg Udi Gddg Ydjg hSde ai dhGRe GdTQY hCMcGeg s
(3BNQgG (B:s
(3jfJgi HYO HGH GdQDjG HhQbJjf HGdMOjK GdTQja (B: (3Yf eYbd Hf jSGQ Yf GdfHi Udi Gddg Ydjg hSde bGd (B: (3GdYHGOI ai GdgQL cgLQI GdfHi ced s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B600s
Keywords: (3Gdabg GdeGdcjs